The Significance of the Activity of the "Turkestan Amateur Archeologist Circle" in the Formation of the Archeology of the Country of Turkestan - Rakhmatullaev Akhadulla Yusupjon ugli (Zien Journals, 2022)
In this article, the factors of formation and development of archeology of the Turkestan region are analyzed, and the role and importance of local archeology circles is highlighted in it.
Keywords: Turkestan; archeologist circle; archeology; source studies